STYLE-SPECIFIC INDIVIDUALITY - Muftullayeva Gavhar Yusupovna (Journals Park Publishing, 2022)
The article discusses the individuality of the style, the innovation of the artist depends on the internal factors that affect him, and analyzes the work of Alisher Navoi “Mahbub ul-kulub” are studied.
Keywords: Style categories, internal and external factors